Faktor-Faktor Yang Mempengaruhi Implementasi Kebijakan Penyelenggaraan Mal Pelayanan Publik - Ratna Puspita Sari; Amy Yayuk Sri Rahayu (PERSPEKTIF, 2021)
This study aims to analyze the factors that influence the Implementation of Public Service Mall Implementation Policies in DKI Jakarta Province. This study uses a policy implementation model proposed by Van Meter and Van Horn (1975) which consists of several factors, namely (1) Policy Standards and Objectives; (2) Policy Sources; (3) Communication between organizations and implementation of Activities; (4) Characteristics of the Implementing Body; (5) Socio-political and economic conditions; and (6) the trend of implementers (implementors). This concept is used to analyze the factors that influence the implementation of public policies. This study uses a post-positivist approach with qualitative research methods in order to explain the factors that influence the implementation of policies on the implementation of public service malls in DKI Jakarta Province. The data collection technique used was triangulation. In general, the research results illustrate that the implementation of Public Service Hall in DKI Jakarta Province has been going well, but there are several factors such as inadequate facilities and infrastructure, characteristics of implementing agencies that have not supported the implementation and communication between organizations and the implementation of activities has not been consistent , thus having an impact on service delivery to the community.